In Situ Bioremediation of Crude Petroleum Oil Polluted Soil Using Mathematical Experimentation - Modupe Elizabeth Ojewumi; Moses Eterigho Emetere; Damilola Elizabeth Babatunde; Joshua Olusegun Okeniyi (International Journal of Chemical Engineering)
Mathematical modelling of in situ (on site) bioremediation of crude petroleum polluted soil was investigated. An unsteady state mathematical model based on bulk flow of oil through the soil and molecular diffusion through the pores of the soil was developed. The parabolic partial differential equation developed was resolved into a system of ordinary differential equations (ODEs) by orthogonal collocation method and the necessary boundary condition was used. The resultant system of ODE was solved using fourth-order Runge-Kutta method. The simulated data gave a good agreement with experimental data.